Fabrication of electrospun nanofibrous clinoptilolite doped thermoplastic polyurethane scaffolds for skeletal muscle tissue engineering - Yildirim, Meryem Akkurt; Sanli, Abdulkadir; Turkoglu, Nelisa; Denktas, Cenk (WILEY, 2023)
The treatment of skeletal muscle, which lost its function with damage or trauma with autologous muscle tissue transfer, is a very problematic approach. Hence, it is critical to develop materials that are mimicking muscle tissue mechanical behaviors and allowing cell adhesion. Polyurethanes (PUs) are one of the most common polymers in tissue engineering applications and skeletal muscle regeneration due to their elasticity and mechanical flexibility. Clinoptilolite (CLN) is a hydrated alumina silica crystal based biocompatible material that numerous positive effects on animal and human health. Here, we report the synthesize of flexible membranes based on clinoptilolite (CLN) doped thermoplastic polyurethane (TPU) nanofiber network to be used in the field of skeletal muscle regeneration. We primarily evaluated their ability to mimic skeletal muscle by determining their mechanical properties and cell adhesion rates. We observe that cell adhesion and proliferation increased with the increase of CLN contribution. Young modulus (E-Y) values of pure TPU, 5 and 10 wt.% CLN-doped TPU fibers are 3.66, 2.37, and 1.85 MPa, respectively. Mechanical elongations at break of pure TPU, 5 and 10 wt.% CLN-doped TPU fibers after 37 degrees C treatment (7th day) are 193.41%, 113.30%, and 197.15%, respectively. With the addition of 5 wt.% CLN, the thermal stability slightly increased compared to the pure TPU and 10 wt.% CLN/TPU. In addition, cytotoxicity studies reveal that CLN/PU membranes are biocompatible, and finally cell adhesion increases proportionally to the increased CLN contribution. The obtained results indicate that the CLN/PU membranes can be used as a skeletal muscle scaffold.
Keywords: clinoptiolite; electrospun nonofibrous; skeletal muscle; thermoplastic polyurethane; MECHANICAL-PROPERTIES; COMPOSITE SCAFFOLDS; REGENERATION; PROLIFERATION; CELLS; BIOMATERIALS; DEGRADATION; ALUMINUM; COLLAGEN; CULTURE; Polymer Science